A Europe‐wide randomized controlled trial of hearing and vision rehabilitation in dementia: Results from the SENSE‐Cog trial. (20th December 2022) - Leroi, Iracema; Camacho, Elizabeth; Chaghil‐Boissier, Nathalie; Charalambous, Anna Pavlina; Conelly, JP; Constantinidou, Fofi; David, Renaud; Elliott, Rachel; Frison, Eric; Hann, Mark; Holden, Alison; Kennelly, Sean; et al.
Abstract: Background: Hearing and vision impairments are highly prevalent in people with dementia (PwD) and may have a negative impact on quality of life and other dementia‐related outcomes. Intervening to optimize sensory function improve these outcomes. The SENSE‐cog Trial evaluated whether a home‐based multi‐part 'sensory support' intervention (SSI) is effective in improving quality of life and other key outcomes in PwD (including hearing and/or vision problems), and their care partners. Methods: This was a pan‐European, multi‐centre, observer blind, randomized controlled trial (RCT), of PwD with hearing and/or vision impairment and their companions. We compared 'care as usual' (CAU) to a multi‐part complex intervention of hearing and vision rehabilitation (SSI) tailored to each participant dyad. The SSI included: assessment and correction of hearing and/or vision impairments; home‐based, therapist‐delivered sensory support (i.e., adherence with devices; improving the sensory environment, communication training, and signposting to other support agencies). Outcomes were collected at baseline, intervention end (18 weeks) and post‐intervention (36 weeks – the primary endpoint) and included: quality of life, sensory and cognitive functional ability, relationship satisfaction, neuropsychiatric symptoms, and mental well‐being. Health resource utilization was measured to estimate cost‐effectiveness of the intervention. Results: Across 7 European centers (UK, France, Cyprus, Greece), 252 participants with dementia (median age 80 years, 53% female, 59% hearing impairment only, 4% visual impairment only and 37% both impairments) were randomized from May 2018 to May 2021 to receive either CAU or SSI (10 visits over 18 weeks). Mitigating strategies to adapt study procedures to the COVID‐19 pandemic were implemented. Over 75% of participants completed the primary outcome, the DEM‐QoL scale, at 36 weeks. An initial feasibility study yielded positive results for this outcome revealing an average improvement in the DEM‐QoL of 4.9 points (> minimum important clinical change). Conclusions: Hearing and vision support in PwD is a potentially important and cost‐effective means of improving the lived experience of dementia, representing a critical step in the diagnostic and care pathway. Main RCT results will be available in May 2022. Trial registration : ISRCTN17056211